O uso de jogos pedagógicos no ensino-aprendizagem e na avaliação de bioquímica para o ensino médio - Miranda, Sulamita Gislene Dias (2019)
This work is result from a qualitative research, a case study, which aims to develop a game that contributes to the teaching and learning of biochemistry, verify differences in this teaching and learning, among those diferences that are linked to the moment of choice in the game application, and verifying i this game could be used for the evalution of biochemical knowledge. This proposal was fulfilled with college students of the chemistry degree course of the Federal University of Goiás, and with students of first year of high school in the state school Damiana da Cunha, in Goiás. The results showed that the teaching and learning of biochemical concepts through the game is efficient. Contributing not only overcome the difficulties encountered in teaching hese concepts, but also to a more meaning full earning of them. In relation to the evaluation, the game proved to be na excelente instrument for evaluting both the diagnostic and the formative type.